Synthesis and Characterization of Mesoporous SnO2 Photocatalyst for Degradation of Dye and Volatile Organic Compound - Kaur, Mandeep (My University, 2016)
The industrial and domestic waste water effluents from any sources include organic chemicals and pathogens; have maximum pollutants, which can be removed before discharging into the water bodies. One of the major water contaminated pollutant has been measured as methylene blue. Such pollutant is leading in surface water and groundwater. It will cause irreversible hazards to human and aquatic life in present era. Nanotechnology plays a main role in degrading such type of pollutant. In order to fulfill today's requirement, we have decided to handle the ecofriendly green synthesis of nanoparticles and its application by merging important fields like environmental sciences, chemical sciences, and biotechnology. Here our work emphasizes on the single step synthesis of mesoporous SnO2 nanoparticles (SnO2 NPs), and it was confirmed by various physico-chemical characterization techniques such as UV–visible spectroscopy, FT-IR, XRD, TEM and BET surface area. The obtained results stated that the synthesized SnO2 NPs were in spherical shape with an average size of 2-5 nm, which resulted in a product of nanotechnology. Further, we have utilized the eco-friendly synthesized mesoporous SnO2 NPs photocatalytic degradation of environmental concern methylene blue with first-order kinetics and volatile organic compound (chlorobenzene) showed excellent activity on 0.075 M of SnO2 NPs due to its reduced crystallite size and high surface area. Mesoporous SnO2 (m-SnO2) nanoparticles prepared by using only pure surfactant had less surface area as compared to prepared by mixture of cationic and anionic surfactants. Photodegradation of methylene blue (83%) and chlorobenzene (92.7%) was found to be efficient by using m-SnO2 NPs. From our studies, m-SnO2 nanoparticles showed excellent photocatalytic efficiency making it a promising photocatalyst for degradation of dyes and volatile organic compounds.
M Sc Dissertation
Keywords: photodegradation of volatile organic compound; dye